Zarys dziejów Biblioteki Uniwersyteckiej w Poznaniu. Informator - Chachlikowska, Aldona; Jazdon, Krystyna; Szulc, Aleksandra; Wieland, Hanna (Biblioteka Uniwersytecka w Poznaniu, 2011)
Praca przygotowana została z okazji obchodów 400-lecia tradycji uniwersyteckich w Poznaniu oraz w Dekadzie Jubileuszowej Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2009-2019

The present guide has been prepared in recognition of the City of Poznań’s four hundred year academic tradition and the celebration of the 100th anniversary of Adam Mickiewicz University in Poznań.
An outline of the history of Poznan University Library. A guide
Keywords: Biblioteka Uniwersytecka w Poznaniu